Knowledge, Attitude and Practices towards Condom Use among Students of Kampala School of Health Sciences, Wakiso District. A Cross-sectional Study - Mukenye , Ayub (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess the knowledge, attitude, and practices towards condom use among students of Kampala school of health sciences, Wakiso district. Methodology: The study adopted a cross-section design to address the specific objectives of the study on a sample of 50 respondents using a simple random technique. A self-administered questionnaire with both open and ended questions was designed and used as a data collection tool, data was analyzed manually by use of pens, tally sheets, and a calculator; presented in form of percentages, tables, bar graphs, and pie-charts using the Microsoft excel computer program. Results: Overall findings revealed that; (96%) of the study respondents ever heard about condoms, (44%) obtained information about condoms from friends, (60%) knew both condoms, (and 86%) indicated that there was no access to get condoms at school, (76%) knew how to use a condom and (66%) knew that condom use prevents HIV/AIDS transmission and other STIs. Conclusion: The researcher concluded that even though the study participants exhibited knowledge towards condom use with a slightly negative attitude, the practices towards condom use were not pleasing since most of the respondents ever had sex with multiple sexual partners and most of the participants did not frequently use a condom during sexual intercourse which increases the risk of acquiring STIs and unwanted pregnancies. Recommendation; The researcher, therefore, recommended that the administration of KSHS should provide free accessibility of condoms to students and also continue with general sensitization of students about youth-friendly sexual and reproductive health programs, this will improve the condom use practices hence curbing the risk of acquiring STIs including HIV and unwanted pregnancies.